Orientalist Objections to the Problematic Verses of the Qur'an in the Context of Abrogation (Naskh) and Qur'anic Readings (Qirāʾāt) - Dr. Muhammad Mumtaz Ul Hasan; Dr.Muhammad Pervaiz (Journal of Religion and Society, 2025)
The Noble Qur'an is the final Divine Book of guidance revealed by Allah, the Almighty, to the Seal of the Prophets, Muhammad al-Mustafa ﷺ. It has been established as the eternal source of religious, moral, and spiritual guidance for all of humanity until the Day of Judgment. The eloquence, miraculous nature, and legislative wisdom of this Glorious Book have remained a subject of deep reflection and intellectual engagement for scholars and seekers of insight throughout the centuries. Within the Islamic scholarly tradition, disciplines such as Qur'anic exegesis (tafsīr), the principles of jurisprudence (uṣūl al-fiqh), Qur’anic readings (qirāʾāt), and the theory of abrogation (naskh) have been thoroughly studied, offering a principled framework for understanding, interpreting, and applying the Qur’an.However, Orientalists have taken these very academic discussions and reinterpreted them as grounds for casting doubt upon the Qur'an. Under the broad label of “problems in the Qur'an” (mushkilāt al-Qur'ān), they have raised a range of objections targeting the internal coherence, semantic harmony, and revelatory nature of the Qur'an. One of the major points of critique revolves around the concepts of naskh fī al-Qur'ān (abrogation within the Qur'an) and qirāʾāt Qurʾāniyyah (variant Qur'anic readings). Orientalists assert that Muslims later invented the principle of abrogation as a justification for the so-called contradictions in the Qur'an. According to them, this principle served to rationalize or legalize the apparent divergences in various commandments and statements.The Orientalists did not treat the issue of abrogation merely as a topic of academic inquiry, but rather used it to challenge the very authenticity and divine nature of Islamic revelation. They argued that, much like human lawmakers who alter laws in response to changing times and emerging circumstances, Muslims too amended their divine laws over time. Thus, if abrogation is to be considered an act of God, it would, in their view, imply a deficiency in divine knowledge, since a perfect legislator should have no need for revision or correction.On the basis of this assumption, Orientalists have cleverly ascribed the concept of abrogation to the Prophet Muhammad ﷺ himself, attempting to portray the phenomenon of verse replacement or amendment as a human initiative or prophetic reconsideration rather than divine revelation. Similarly, the multiplicity of Qur’anic readings (qirāʾāt) has also been exploited by them as evidence of textual instability and variation within the Qur'an. Keywords: Orientalist, Objections, Problematic, Abrogation, Established, Jurisprudence, Phenomenon